The effect of the common determinants factors on the clinical aspects of pityriasis versicolor from Missan province - Abdulrassol, Fadhil Abbas ((Humanities, social and applied sciences) Misan Journal of Academic Studies, 2019)
Introduction and objective: Pityriasis (tinea) versicolor is a mild, chronic infection of the skin caused by Malassezia yeasts, and characterized by discrete or confluent, scaly oval to round macules scattered over characteristic areas of the body, including the upper trunk, neck, and upper arms. The color of patches varies from almost white to pink to reddish brown or fawn colored. The aim of the present study is to assess the effect of the common determinants factors on the clinical aspects of pityriasis versicolor in Missan province. Patients and methods: The study sample consist of 300 patients with pityriasis versicolor attending the Department of Dermatology in Al-Sader Teaching Hospital in Missan province during the period from October 2015 to March 2016.The diagnosis of pityriasis versicolor was done by clinical examination and established by woods lamp of the skin lesion and 10% KOH examination of scraping from skin lesion for suspected cases. Results: out of, 300 patients with pityriasis versicolor, there were 180 males and 120 females. The ages of patients ranged from 10 to above 60 years. The majority of cases 43% fall in age group of 20-29 years. The majority of cases came from urban areas (63.4%) compared to (36.6%) from rural areas. The indoor patients were 165 and outdoor patients were 135 with 48.3 % presented with hyperpigmentation, followed by 40% with hypopigmentation, 6.7% mixed and 5% erythematous. The time of onset in summer 55% compared to 45% in winter. Asymptomatic individuals were 56.7% while who complaining from mild pruritus were 43.3% with 51.47% were chronic cases compared to 48.3%were acute cases. The nonexposed area trunk (45%) infected more than exposed area (25%) and (30%) was mixed areas.